Retrograde signaling from functionally heterogeneous plastids - Lepistö, Anna; Toivola, Jouni; Nikkanen, Lauri; Rintamäki, Eevi (Frontiers in Plant Science, 2012)
Structural and functional components of chloroplast are encoded by genes localized both to nuclear and plastid genomes of plant cell. Development from etioplasts to chloroplasts is triggered by light receptors that activate the expression of photosynthesis-associated nuclear genes (PhaNGs). In addition to photoreceptor-mediated pathways, retrograde signals from the chloroplast to the nucleus activate or repress the expression of nuclear genes involved in acclimatory or stress responses in plant leaves. A plant mesophyll cell contains up to one hundred chloroplasts that function autonomously, raising intriguing questions about homogeneity and coordination of retrograde signals transmitted from chloroplast to nucleus. We have previously demonstrated that the knockout of the chloroplast regulatory protein, CHLOROPLAST NADPH-DEPENDENT THIOREDOXIN REDUCTASE (NTRC) leads to a heterogeneous population of chloroplasts with a range of different functional states. The heterogeneous chloroplast population activates both redox-dependent and undifferentiated plastid-generated retrograde signalling pathways in the mutant leaves. Transcriptome data from the ntrc knockout lines suggest that the induction of the redox-dependent signalling pathway depends on light conditions and leads to activation of stress-responsive gene expression. Analysis of mutants in different developmental stages allows to dissect signals from normal and anomalous chloroplasts. Thus, the signals derived from anomalous chloroplasts repress expression of PhaNGs as well as genes associated with light receptor signalling and differentiation of stomata, implying interaction between retrograde pathways and plant development. Analysis of the nuclear gene expression in mutants of retrograde signalling pathways in ntrc background would reveal the components that mediate signals generated from heterogeneous plastids to nucleus.